Assembling traces, or the conservation of net art - Dekker, Annet (Revista do Colóquio, 2022)
This paper explores the challenges and methodologies of conservation for net.art works. It discusses how the ephemeral and dynamic nature of net.art complicates its preservation. This complexity is exemplified by Martine Neddam’s project "Mouchette.org", an interactive work that evolves with the participation of the public. It suggests that the conservation of net.art should go beyond material preservation and adopt an approach that allows the continuity and adaptation of the work in response to technological and cultural changes. The concept of "traces" is central and represents parts that testify to the existence of the work overtime. It is concluded that the conservation of net.art should be procedural, collaborative, and allow it to maintain its relevance and authenticity, even in the face of constant technological and cultural transformations.